The pirates of Somalia : maritime bandits or warlords of the high seas - Cronje, Dian (Stellenbosch : University of Stellenbosch, 2010)
Thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Political Management) at Stellenbosch University